2021
DOI: 10.1038/s41562-021-01107-7
|View full text |Cite
|
Sign up to set email alerts
|

Payoff-based learning best explains the rate of decline in cooperation across 237 public-goods games

Abstract: What motivates human behaviour in social dilemmas? The results of public goods games are commonly interpreted as showing that humans are altruistically motivated to benefit others. However, there is a competing 'confused learners' hypothesis: that individuals start the game either uncertain or mistaken (confused), and then learn from experience how to improve their payoff (payoff-based learning). We: (1) show that these competing hypotheses can be differentiated by how they predict contributions should decline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(73 citation statements)
references
References 70 publications
6
67
0
Order By: Relevance
“…1a. Which social learning strategies, if any, do participants use?-We predict that payoff biased learning will have the strongest influence on cooperative behaviour [45] followed by prestige and then conformity [38,42,43]. 2a.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1a. Which social learning strategies, if any, do participants use?-We predict that payoff biased learning will have the strongest influence on cooperative behaviour [45] followed by prestige and then conformity [38,42,43]. 2a.…”
Section: Resultsmentioning
confidence: 99%
“…Further experimental evidence suggests that participants are more likely to exhibit a payoff bias than conformity in a cooperation game and reduce their contributions [42,43] and also decrease their contributions when reminded how their behaviour was benefiting others [44]. A recent analysis of 237 PGGs also showed that declines in contributions were most consistent with improving personal payoffs [45]. Furthermore, cooperation was also higher when participants had no information on the behaviour of their group mates [46].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We wanted multiple rounds of 'model' data so that we could observe more learning and short-term cultural evolution. However, contributions normally decline in public goods games [32]. If individuals observe declining levels of cooperation, it is hard to test if individuals are learning from success or trying to match a declining group average [36,50].…”
Section: (C) Previous Experimentsmentioning
confidence: 99%
“…In the public goods game, individuals can make monetary contributions to a group fund. Financially speaking, the group does best if everyone contributes fully, but individuals do best by contributing nothing, hence the social dilemma [28][29][30][31][32]. Many studies have shown that individuals tend to contribute partially and that most will condition their cooperation to local levels (either perfectly or imperfectly) [2,[33][34][35][36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%